2007
DOI: 10.1029/2007ja012354
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal structures of substorm electron injection and their signatures in riometer observations

Abstract: [1] We propose a theoretical model to investigate the effects of the curvature/gradient (c/g) drift and the finite azimuthal extent of the dipolarization region on the electron injection process associated with the substorm dipolarization. We study the azimuthal structure of high-energy (>30 keV) electron precipitation flux and compare the result with riometer observations. We are able to reproduce three basic archetypes of riometer responses to substorms, namely, the spike, dispersionless injection, and dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 41 publications
(100 reference statements)
5
46
0
Order By: Relevance
“…The events at short distances in Figure 1b that were associated with negative time delays in Figure 3a, were often located near 23 MLT. Liang et al [2007] showed that a significant number of dispersionless injections occurred near 23 MLT and thus these observations are likely to be within the DP region.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The events at short distances in Figure 1b that were associated with negative time delays in Figure 3a, were often located near 23 MLT. Liang et al [2007] showed that a significant number of dispersionless injections occurred near 23 MLT and thus these observations are likely to be within the DP region.…”
Section: Discussionmentioning
confidence: 89%
“…The injected electrons move with gradient and curvature (GC) drift to the east of the onset and as the drift angular velocity depends on the particle energy, the signature becomes more and more “dispersed” (different risetimes for different energies) the further to the east of onset it is observed. If the finite azimuthal extent of the dipolarization region is taken into account, a spike signature west of the substorm onset can also be reproduced by modeling [ Liang et al , 2007].…”
Section: Introductionmentioning
confidence: 99%
“…The location of these spikes within the dispersionless injection region has previously been modelled by Liang et al (2007). In that study, spikes where shown to be a direct consequence of drift loss/leakage of electrons from a dipolarizing flux tube.…”
Section: Discussionmentioning
confidence: 99%
“…This causes a characteristically short timescale rise and fall in riometer absorption (the "spike") which is significantly shorter than the normal decay driven by precipitation. Typically the conditions for absorption spikes are met on the western edge of the injection region, in this event that is not the case, which may suggest a "successively emerging dipolarization structure toward the morning sector" (Liang et al, 2007). In this model, each spike is a sudden rise indicative of a physical "jump" in injection region location and the decay results for a drifting population without further sources.…”
Section: Discussionmentioning
confidence: 99%
“…For a number of events, they found that a sharp rise in plasma sheet electron flux for energies >30 keV (dispersionless injection) was often accompanied (under certain conditions) by a sharp rise in riometer absorption due to sudden enhancement of ionization in the lower ionosphere. If multiple riometers pick up this ionospheric signature of high energy particle precipitation, then tracking the movement of these signatures can give insight into the spatial and temporal evolution of the substorm injection region [Berkey et al, 1974;Liang et al, 2007;Liu et al, 2007;Spanswick et al, 2009]. In this study, we extend this ground-based method of identifying substorm precipitation signatures to GPS TEC, assuming that enhanced electron density due to high-energy particle precipitation will produce detectable TEC enhancements.…”
Section: Introductionmentioning
confidence: 99%